2017
DOI: 10.3389/fmicb.2017.01577
|View full text |Cite
|
Sign up to set email alerts
|

First Molecular Detection of Babesia gibsoni in Dogs from Wuhan, China

Abstract: Canine piroplasmosis is a significant disease in dogs caused by Babesia and Theileria parasites. The clinical manifestations range from mild illness to serious disease depending on the parasite species and the physical condition of the infected dog. Canine piroplasmosis has been reported to be prevalent in China. However, no molecular evidence of the disease has been reported in pet dogs from Wuhan. In this study, 118 blood samples were randomly collected from pet dogs in veterinary clinics. The blood samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 39 publications
1
21
2
Order By: Relevance
“…The majority of investigations of canine piroplasmosis have been performed during the spring or autumn, the seasons of highest vector tick activity. It has been previously reported in China that the prevalence of B. gibsoni and B. vogeli is 1.5–11.86% and 1.2–11.3%, respectively [ 9 , 18 , 30 , 33 ]. In 2019, 130 blood samples were randomly collected from pet dogs in Henan Province to investigate the infection status of piroplasms during the winter.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of investigations of canine piroplasmosis have been performed during the spring or autumn, the seasons of highest vector tick activity. It has been previously reported in China that the prevalence of B. gibsoni and B. vogeli is 1.5–11.86% and 1.2–11.3%, respectively [ 9 , 18 , 30 , 33 ]. In 2019, 130 blood samples were randomly collected from pet dogs in Henan Province to investigate the infection status of piroplasms during the winter.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, if one considers the global distribution of B. gibsoni , some epidemiological findings need to be mentioned. Babesia gibsoni is widespread throughout the Oriental region, for instance in China [ 43 ]. However, cases of canine babesiosis caused by B. gibsoni have been reported outside the distributional range of its main vector tick, H. longicornis , incriminating other ticks for its transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that it can spread through ticks, blood transfusion, and placenta (2, 3). In 2017, He et al reported the strain of B. gibsoni in Wuhan and provided the molecular biological evidence such as 18S rRNA and ITS gene sequence, confirming the epidemic of Babesia in Wuhan from the evolutionary point of view (4).…”
Section: Introductionmentioning
confidence: 94%